NILAI KECERNAAN BAHAN KERING DAN BAHAN ORGANIK Samia cynthia ricini INSTAR 5 YANG DIBERI PAKAN DAUN KETELA POHON - Gobai, Orgens; Iskandar, Ahmad; Susanti, Sri (Universitas Tribhuwana Tunggadewi, 2018)
The quality of cassava leaves of different varieties will affect the growth of silk worm instar 5, cocoon quality, and quality of the resulting fiber. To increase the production of coconut so cassava leaves required superior can be used as silkworm feed. The purpose of the study was to determine the amount of digestibility and consumption of different varieties of cassava leaves, on the growth of silkworms. The method used in this research is the Randomized Complete Random Design (RAL) method, followed by BNT test in the direction of 3 treatment pattern, the treatment (P1) cassava leaves of varieties faroka, the treatments (P2) cassava leaves shrimp varieties and P3 leaves of cassava varieties rubber. The results of the study showed that the consumption and digestibility of dry matter and organic matter was very significant (P